Bibliography: islamic State : (IS, ISIS, ISIL, Daesh) : Part 7 - Tinnes, Judith (Perspectives on terrorism, 2023)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on the Islamic State (IS/ISIS/ISIL/Daesh) and its predecessor organisations. To keep up with rapidly changing events on the ground and in the jihadist online ecosystem, the most recent publications have been prioritised during the selection process. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.